2020
DOI: 10.3389/fcvm.2020.584727
|View full text |Cite
|
Sign up to set email alerts
|

Neural-Network-Based Diagnosis Using 3-Dimensional Myocardial Architecture and Deformation: Demonstration for the Differentiation of Hypertrophic Cardiomyopathy

Abstract: The diagnosis of cardiomyopathy states may benefit from machine-learning (ML) based approaches, particularly to distinguish those states with similar phenotypic characteristics. Three-dimensional myocardial deformation analysis (3D-MDA) has been validated to provide standardized descriptors of myocardial architecture and deformation, and may therefore offer appropriate features for the training of ML-based diagnostic tools. We aimed to assess the feasibility of automated disease diagnosis using a neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Using automated disease identification to distinguish HCM from states that mirror it, such as CA, Anderson–Fabry disease, and hypertensive cardiomyopathy, was the goal of one study (HTNcm). To distinguish between HCM and other situations, a fully connected layer feed-forward neural network was developed [ 102 ]. This study revealed that it is possible to diagnose cardiomyopathy states using only 3D-MDA and that it is capable of differentiating between HCM and similar disease states.…”
Section: Diagnosis Of Amyloidosismentioning
confidence: 99%
“…Using automated disease identification to distinguish HCM from states that mirror it, such as CA, Anderson–Fabry disease, and hypertensive cardiomyopathy, was the goal of one study (HTNcm). To distinguish between HCM and other situations, a fully connected layer feed-forward neural network was developed [ 102 ]. This study revealed that it is possible to diagnose cardiomyopathy states using only 3D-MDA and that it is capable of differentiating between HCM and similar disease states.…”
Section: Diagnosis Of Amyloidosismentioning
confidence: 99%
“…Cardiac magnetic resonance imaging (MRI) can detect cardiac involvement even when the LVH severity is mild, allowing to reclassify 21% of FD patients as having cardiac involvement that was previously unrecognized [ 38 ]. Of note, recent studies have suggested that machine learning applied to 3D myocardial architecture and deformation obtained by cardiac MRI may present increased ability to perform differential diagnosis of the cause of HCM [ 39 ].…”
Section: Cardiac Manifestations Of Fdmentioning
confidence: 99%
“… 4 Commercial software (cvi42, Circle Cardiovascular Imaging) was used for all measurements except 3D-MDA, performed using previously validated software. 2 Volumes were indexed to height, given the anticipated change in weight during the event.…”
Section: Investigationsmentioning
confidence: 99%
“…Such events present a unique opportunity to study the impact of extreme physiological demand on cardiac tissue health, chamber remodeling, contractile performance, and their resultant influence on cardiac hemodynamics. Contemporary cardiac magnetic resonance (CMR) imaging provides the unique capacity to study these in a single setting through the use of tissue mapping, 1 3-dimensional myocardial deformation analysis (3D-MDA), 2 and 4-dimensional flow analysis (4D-flow). 3 In this case report, we performed serial CMR evaluations in a 37-year-old athlete who ran 2.469 km to raise awareness for rare disease research.…”
mentioning
confidence: 99%